Application of DPFGSE-ROE to calixarene derivatives under conditions near NOE zero-crossing - Bauer, Walter; Soi, Antonio; Hirsch, Andreas (Magnetic Resonance in Chemistry, 2000)
In a modification of the well-established DPFGSE-NOE method, the mixing period is replaced by a spin-lock sequence (DPFGSE-ROE). Similar to conventional one- and two-dimensional ROE applications, the NOE is positive throughout, irrespective of the molecular correlation time. For the two calixarene derivatives 1 and 2 conventional difference NOE spectroscopy and DPFGSE-NOE yield negative NOEs, indicating ωτ > 1.12. By contrast, DPFGSE-ROE leads to strong positive enhancements. Indirect (transferred) NOEs may be identified by their negative sign under these conditions. Copyright © 2000 John Wiley & Sons, Ltd.